A defect-resistant Co–Ni superalloy for 3D printing - Sean P. Murray (Nature Portfolio, 2020)
Additive manufacturing promises a major transformation of the production of high economic value metallic materials. Here, the authors describe a new class of 3D printable superalloys that are amenable to crack-free 3D printing via electron beam melting as well as selective laser melting.